(3bUGFOs - (3WQaI Hf GdYHO GdHcQjs ((3eMehO Hdi s)
(3ChdgG (B:s
(3Cef Ce Chai OefI de Jcde HMheGfg GdOQGL hGdedJKe s
(3BNQgG (B:s
(3Ef jTJchG NWHkG Jcf eQhAJg Ch jQJLhG YXei GdQZGFH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B2 - (3U(B31s
(3GdfSNI HgG MhGTs
(3eeG QhGg GdCUeYj hCHhYeQh hGdeaVds
(3hHgG TQhM hfXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B102 s
Keywords: (3GdCOHs